Analisa Alarm pada Device Proteksi Generator dan Transformer PLTU Jawa 7 Terhadap Grounding Fault yang Terjadi di SUTET Outline LBE Line I 500kV - Ahmad Ilham Kamal; Nur Rahma Dona (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2023)
In every PLN 500kV grid system power plant in Jamali (Java-Madura-Bali) it is connected in parallel between the generators with a substation as a connector. The function of the substation itself is to equalize the voltage between generators. The case in this journal is the 500kV grid and also functions as a breaker area when a disturbance (short circuit) occurs at a certain point, which will make the 500kV system remain reliable so that it can always distribute electricity to consumers. Analysis of alarms in the generator protection system when a disturbance occurs on the outside of the power plant functions to ensure that the protection equipment in the unit is functioning normally or not, and functions to ensure that the fault location point is not in the internal electrical system of the power plant, and also functions to ensure that the outline protection relay is working. normally according to calculations and design.